The apoM/S1P Complex—A Mediator in Kidney Biology and Disease? - Bisgaard, Line S.; Christoffersen, Christina (Frontiers in Medicine, 2021)
Kidney disease affects more than 10% of the population, can be both acute and chronic, and is linked to other diseases such as cardiovascular disease, diabetes, and sepsis. Despite the detrimental consequences for patients, no good treatment options directly targeting the kidney are available. Thus, a better understanding of the pathology and new treatment modalities are required. Accumulating evidence suggests that the apolipoprotein M/sphingosine−1-phosphate (apoM/S1P) axis is a likely drug target, but significant gaps in our knowledge remain. In this review, we present what has so far been elucidated about the role of apoM in normal kidney biology and describe how changes in the apoM/S1P axis are thought to affect the development of kidney disease. ApoM is primarily produced in the liver and kidneys. From the liver, apoM is secreted into circulation, where it is attached to lipoproteins (primarily HDL). Importantly, apoM is a carrier of the bioactive lipid S1P. S1P acts by binding to five different receptors. Together, apoM/S1P plays a role in several biological mechanisms, such as inflammation, endothelial cell permeability, and lipid turnover. In the kidney, apoM is primarily expressed in the proximal tubular cells. S1P can be produced locally in the kidney, and several of the five S1P receptors are present in the kidney. The functional role of kidney-derived apoM as well as plasma-derived apoM is far from elucidated and will be discussed based on both experimental and clinical studies. In summary, the current studies provide evidence that support a role for the apoM/S1P axis in kidney disease; however, additional pre-clinical and clinical studies are needed to reveal the mechanisms and target potential in the treatment of patients.